The warlords of Nin - Lawhead, Stephen R. (Avon Books, 1983)
When an omen of dire evil in the form of Nin the Destroyer threatens to shatter the ten-year peace of Mensandor, Quentin, the brave man who had helped the now dead Dragon King reclaim his throne, is chosen by destiny to save the realm. Reprint.